Martibo: Smart Tissue Dispenser with Monitoring Dashboard - Alfaniza, Izzat Muhammad; Syafiq, Muhammad; Ana Ratna Wati, Dwi; Wisudawan, Hasbi Nur Prasetyo; Ming, Eileen Su Lee; Addi, Mitra Binti Mohd (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
This paper presents Martibo, a smart tissue dispensing management system integrated with a smartphone based on the Internet of Things (IoT), to improve tissue usage efficiency in public spaces and households. The system uses sensors to detect tissue availability and sends notifications to the Blynk application. The system is evaluated based on reliability, accuracy, and user interface responsiveness. The results show high accuracy with an average error of 0.91% in tissue availability detection and an average notification response time of 1.2 seconds. The system transmits data accurately through a Wi-Fi connection, enhancing the convenience and efficiency of tissue usage. The advantages of this system include accurate real-time data, a user-friendly interface, and good integration with mobile devices, making it an ideal solution for efficient tissue management.